PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS KANTONG PERKALIAN DALAM MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS IV UPTD SDN 187 BARU - Idris, Desi Rahmawati; Ismail, Nurmaimanah; Rahmawati Idris, Desi; Syahrani Putri, Nurqiyah; Nurlianti, Nurlianti; Sirajuddin, Sirajuddin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This study aims to improve the learning outcomes of fourth-grade students at UPTD SDN 187 Barru in Mathematics by using multiplication pouch-based learning media. The research method used in this study is Classroom Action Research (CAR), which was conducted in two cycles, each consisting of four meetings. The first and second cycles aimed to evaluate the application of the multiplication pouch media in Mathematics teaching and improve students' understanding of the concepts being taught. The results of the study showed that in the first cycle, the average student learning score reached 74.5, with classical completeness at 84.21%. In the second cycle, a significant improvement occurred with an average score of 81.5 and classical completeness reaching 115.79%, meaning all students achieved the Minimum Mastery Criteria (KKM) of 70. Based on these results, it can be concluded that the use of multiplication pouch-based media can enhance the Mathematics learning outcomes of fourth-grade students at UPTD SDN 187 Barru. This study highlights the importance of using creative media in Mathematics instruction to improve students' motivation, interest, and learning outcomes.